2005
DOI: 10.1136/gut.2003.037085
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance colonography for the detection of inflammatory diseases of the large bowel: quantifying the inflammatory activity

Abstract: Introduction: The purpose of this study was to assess the diagnostic accuracy of magnetic resonance colonography (MRC) for its ability to detect and quantify inflammatory bowel disease (IBD) affecting the colon. Endoscopically obtained histopathology specimens were used as the standard of reference. Materials and methods: Fifteen normal subjects and 23 patients with suspected IBD of the large bowel underwent MRC. Three dimensional T1 weighted data sets were collected following rectal administration of water pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
73
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 65 publications
(49 reference statements)
5
73
0
8
Order By: Relevance
“…However, using this criterion as an indicator of inflammation, overestimation of disease was seen in colonic segments. In another recent study (30), the mean SNR of colonic bowel segments measured in healthy volunteers was found to fluctuate after administration of intravenous contrast medium, displaying highest values in the rectum and lowest in the ascending colon. Although the correlations between segmental CDEIS and respectively enhancement and bowel wall thickness indicate that these are important parameters for determining disease activity, the large interobserver variability regarding these parameters in our study, in addition to the results of the above-mentioned studies, indicate that there is a need for large (multicenter) studies on MRI of CD in order to be able to determine accurate criteria for disease activity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, using this criterion as an indicator of inflammation, overestimation of disease was seen in colonic segments. In another recent study (30), the mean SNR of colonic bowel segments measured in healthy volunteers was found to fluctuate after administration of intravenous contrast medium, displaying highest values in the rectum and lowest in the ascending colon. Although the correlations between segmental CDEIS and respectively enhancement and bowel wall thickness indicate that these are important parameters for determining disease activity, the large interobserver variability regarding these parameters in our study, in addition to the results of the above-mentioned studies, indicate that there is a need for large (multicenter) studies on MRI of CD in order to be able to determine accurate criteria for disease activity.…”
Section: Discussionmentioning
confidence: 90%
“…However, before MRI can be considered an alternative for endoscopy in CD, it should be firmly established that in addition to detecting disease activity, MRI is capable of revealing both the severity and the exact location of disease. A few prospective studies have compared MRI with endoscopy regarding the severity of disease, but only the five most recent of these studies also analyzed the accuracy of MRI for localizing disease (27)(28)(29)(30)(31)(32)(33). The results of these studies were conflicting, and the reported sensitivities and specificities varied widely from approaching endoscopic accuracy to considerable over-or underestimation of disease.…”
mentioning
confidence: 99%
“…Other authors have proposed an MRI-based scoring system for the assessment of inflammatory activity including features of bowel wall thickening, lumen narrowing, and number of periintestinal lymph nodes (9). Although feasible, these evaluation algorithms are rel-atively demanding technically, and this may ultimately limit clinical utilization.…”
mentioning
confidence: 99%
“…The mucosal disease, assessable by endoscopy, represents only the tip of the inflammatory process, whereas the mural and extramural disease, detectable with MRI, is the hidden and submerged part of the inflammation. According to recent studies, MRI has shown the same sensitivity of endoscopy in detecting active intestinal inflammation [5][6][7][8]12].…”
mentioning
confidence: 98%
“…So far, different morphological and functional parameters, both T1-and T2-weighted, have been tested for the assessment of disease activity including wall thickening, degree of wall Gd-enhancement [3-9, 11, 23], T2 mural signal intensity [2, 3, 9, 12, 13], T2 signal of mesenteric fat [2,9], enhancement of local lymph nodes [24], pattern of wall Gd-enhancement [13], increased mesenteric vascularity [24], and curves of Gd-wall enhancement (washin and wash-out curves) [8,10]. Each of these parameters has proved be statistically correlated with the ''biological'', endoscopic, or histological activity [3][4][5][6][7][8][9][10][11][12][13][14]. The review of these results should clarify the value of both T1-and T2-weighted imaging in the evaluation of disease activity.…”
mentioning
confidence: 99%